Avaliação do endométrio de mulheres usuárias de tamoxifeno por câncer de mama: correlação entre achados ultrassonográficos, histeroscópicos e histológicos - Júnia Franco de Oliveira Neves (2023)
Introduction: Tamoxifen (TAM) remains part of the treatment of pre and perimenopausal breast cancer, increasingly used for an extended period, longer than five years. Secondary endometrial thickening is a common finding, with endometrium > 4 mm in 50 to 60% of patients, unrelated to disease. Objective: The objective was to evaluate the correlation between abnormal echographic and hysteroscopic findings of endometrial study with clinical manifestations and histological diagnosis in women with a history of breast cancer and use of TAM. Method: This is a retrospective study in which patients undergoing current or previous treatment for breast cancer and use of TAM, symptomatic or not, were initially evaluated with ultrasonography (US). Altered US was considered if endometrial thickness ≥ 9 mm or presence of intracavitary imaging. The medical records of women who underwent hysteroscopy due to endometrial alteration at US or abnormal uterine bleeding (AUB), with a history of breast cancer and use of TAM, were also reviewed. For data analysis, only postmenopausal patients were included (n=50). A control group was formed by postmenopausal women without a history of breast cancer, with endometrial thickness ≥ 5 mm, intracavitary imaging at US or AUB (n=47). Results: US had good sensitivity in the case group (94.1%) and very unsatisfactory specificity (15.2%) in relation to the final histological result, with 63.6% of false-positives. Hysteroscopy had also high sensitivity (94.1%) and higher specificity than US (72.7%). The percentage of false-positives was 36.0%. Older age was related to altered anatomopathological findings (p=0.036). In the control group, US was also less effective compared to hysteroscopy, but with more cases with altered histopathology. Conclusion: The US correlation with the hysteroscopic image and histology in women using TAM is poor. Although hysteroscopy is more accurate, it should not be used as a screennig method either, in order to avoid unnecessary biopsies. US and hysteroscopy showed similar results in the control group. Hysteroscopy performed on an outpatient basis proved to be very tolerable, with or without biopsy. It was not possible to determine the influence of the time of TAM in the diagnosis of endometrial alterations.